Dynamics of Banyuwangi Boom Port From Colonial to Millennial - Abdilah, Yoga Wisnu; Salsabila, Shofi; Azaalea, Randiga Febrian Murni (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
Boom Beach in Banyuwangi has a long history as an international port and center of economic activity in the past. Over time, this area has experienced a decline in function due to technological advances and shallowing. However, this area has been successfully revived as a sustainable tourism destination that attracts international attention. The development of this area is supported by various parties through cultural promotion, provision of modern facilities, and strategic cooperation. This study aims to understand the history, development, and development strategies of Boom Beach as a sustainable tourism destination, as well as to identify factors that support its success in improving the economy and welfare of the local community. The methods used in this study include a literature review and a historiographic approach to analyze qualitative data related to the history and development of the area. Source verification was carried out internally and externally, and data interpretation was carried out qualitatively to compile a comprehensive narrative. The results of the study show that the development of Boom Beach has succeeded in increasing tourist visits through various cultural events and media promotions. Modern port and marine tourism facilities have contributed to this success, including a sustainable area development plan and collaboration between various parties. This success has had a positive impact on improving the local economy and empowering the local community, while maintaining the preservation of the area's culture and economic potential.